The Effect Of Liquidity And Leverage On Profitability In Manufacturing Companies In The Healthcare Sub-Sector Listed On The Indonesia Stock Exchange - Irfan Irfan; Fatimah Zahra (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
The purpose of this study is to examine and analyze the effect of liquidity and leverage on profitability in manufacturing companies in the healthcare sub-sector listed on the Indonesia Stock Exchange during the 2022-2024 period. In this study, the author used an associative approach with quantitative research and secondary data sources obtained from the companies' annual financial reports published on the Indonesia Stock Exchange. Data collection used documentation. The sampling technique used census sampling, resulting in a sample of 30 observations. The data analysis techniques used in this study included descriptive statistics, classical assumption tests, multiple linear regression, hypothesis testing, and coefficient of determination tests using SPSS. The results indicate that partially, liquidity has a positive and significant effect on profitability, while leverage has no significant effect. Simultaneous results indicate that both liquidity and leverage have a positive and significant effect on profitability.